Artificial microRNAs as antiviral strategy to FMDV: structural implications of target selection - Gismondi, Maria Ines; Ortiz, Xoana P.; Curra, Anabella Paola; Asurmendi, Sebastian; Taboga, Oscar Alberto (2018)
RNA interference (RNAi) appears as a promising strategy to control virus replication. While the antiviral power of short-hairpin RNAs or small-interfering RNAs against FMDV has been demonstrated widely, safer RNAi effectors such as artificial microRNAs (amiRs) have not been evaluated extensively. In this work, transgenic monoclonal cell lines constitutively expressing different amiRs targeting FMDV 3D-coding region or 3′UTR were established. Certain cell lines showed an effective, sequence-specific amiR-mediated silencing activity that was accomplished by degradation of the target mRNA, as demonstrated in co-transfection experiments of reporter genes fused to FMDV target sequences. However, FMDV replication in these amiR-expressing cells was affected barely. Experiments aimed at elucidating the cause of RNAi failure demonstrated limited accessibility of the targeted region in the molecular environment of the viral RNA. Since RNAi is mediated by large-dimension silencing complexes containing the siRNA and not simply by a linear oligonucleotide, we propose that target selection should consider not only the local RNA structure but also the global conformation of target RNA.